2007
DOI: 10.4018/jebr.2007100106
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Inhibitors to XBRL adoption

Abstract: The eXtensible business reporting language is an XML-based standard, which has the potential to significantly improve the efficiency and effectiveness of intra- and inter-organizational information supply chain. In this article, we present the case for using convergent interviews as an appropriate and efficient method for modelling factors impacting the adoption of emerging and under-researched innovations, such as XBRL. Using this method, we identify environmental, organizational and innovation-related factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 27 publications
7
24
0
Order By: Relevance
“…According to David (2016), the perceived instability of the XBRL specification and taxonomy is a barrier for XBRL adoption. Similar to earlier XBRL adoptions in Australia, Troshani and Rao (2007) had noticed that unstable XBRL specifications were a major inhibitor to XBRL adoption. Furthermore, Doolin and Troshani (2007) suggested that a high degree of change creates uncertainty in an innovation, thus, reducing the willingness of organisations to experiment with or invest in the new technology and effectively hindering its adoption.…”
Section: Officer C2supporting
confidence: 62%
“…According to David (2016), the perceived instability of the XBRL specification and taxonomy is a barrier for XBRL adoption. Similar to earlier XBRL adoptions in Australia, Troshani and Rao (2007) had noticed that unstable XBRL specifications were a major inhibitor to XBRL adoption. Furthermore, Doolin and Troshani (2007) suggested that a high degree of change creates uncertainty in an innovation, thus, reducing the willingness of organisations to experiment with or invest in the new technology and effectively hindering its adoption.…”
Section: Officer C2supporting
confidence: 62%
“…Moreover, XBRL adoption offers a competitive advantage to XBRL adopters (Pinsker & Li, 2008). Troshani and Doolin (2005) suggested that XBRL is perceived as a form of competitive advantage in relation to increased quality and efficiency. Similarly, Cordery et al (2011) identified a relative advantage to influence the decision of companies to adopt XBRL in New Zealand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, with the involvement of various parties during the adoption process, the process becomes more complex, thus, sufficient and capable expertise is needed to handle emerging issues. Various researchers have agreed that the issue of complexity is one of the challenges faced when adopting XBRL (Troshani & Doolin, 2005;Troshani & Rao, 2007) as complexity of XBRL taxonomy and specifications could diminish XBRL usefulness (Bartley, Chen & Taylor, 2011). In the case of non-adoption, David (2016) found that complexity influences the organisation to abandon XBRL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…and Cordery et al (2011) suggest that a governmental mandate is needed in different countries before XBRL becomes more widely used. Several other studies , Troshani and Rao (2007), Ghani et al (2009), Azam and Taylor (2011)) have examined many aspects of the XBRL phenomenon including adoption strategies, technological innovations, variations in adoption, user perceptions, gaps and misfits, and complexities associated with XBRL implementation. Yoon et al (2011) examine whether or not XBRL adoption reduces information asymmetry in the Korean stock market.…”
Section: Literature Reviewmentioning
confidence: 99%